Linear and nonlinear optical discussions of nanostructured Zn-doped CdO thin films - Yahia, I. S.; Salem, G. F.; Iqbal, Javed; Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2017)
Here, we report the doping effect of zinc (Zn) on the physical properties of cadmium oxide (CdO) at various concentrations (1, 2, 3 and 4 wt% of Zn). The studied samples were prepared using sol-gel in addition with sol gel spin coating technique. The structural, optical and dispersive properties were compared with the already reported work in the literature. The structural properties were observed by using atomic force microscopy (AFM). The AFM images show that the grain size decreases with increasing the concentration of Zn. The highest value of average cluster size (78. 71 nm) was found at 1% and the lowest (60.23 nm) when the doping concentration of Zn was 4%. Similar trend was observed in the roughness of the doped thin film when the Zn concentration was increased. The optical properties were examined using Shimadzu UV-Vis-NIR spectrophotometer and we found that the optical band gap of the un-doped CdO and the Zn-doped CdO thin films increases from 2.54 to 2.62 eV as the Zn concentration is increased from 1% to 4%. Also, the optical dispersion parameters (E-o, E-d, n(infinity)(2), lambda(0) and S-o) were calculated and discussed. We observed that the refractive index dispersion of undoped CdO and the Zn-doped CdO thin films follow the single oscillator model. Finally, spectroscopic method has been exploited to analyze the 3rd order non-linear optical susceptibility chi((3)) and nonlinear refractive index n((2)).
Keywords: Nano-crystalline Zn-doped CdO; Sol-gel spin coating method; Surface morphology; Optical constants; Optical dispersion parameters; Nonlinear optics